Evolution of traditional taboos in Suriname (Sustainability in Debate, 2024)
Traditional taboos have persisted in Suriname, thanks to the sustainability of African culture in Maroon communities in the interior of the country. A conceptual dichotomy emerged in the 19th and early 20th centuries coinciding with two geographical regions: in the coastal region, ‘trefu’, a food taboo, practised mainly by Creoles, violation of which was thought to result in contracting leprosy, and in the interior ‘tyina’, a ‘broader’ taboo concept (food, places, actions) practised by Maroons. Recent research indicates the dichotomy is weakening, reflected in a declining belief in the trefu-leprosy relation and a merging of ‘trefu’ and ‘tyina’, exchange of taboo practices between ethnic groups and declining adherence of youngsters to taboos. The migration of Maroons to the coastal region and creolisation appear to be driving forces behind these processes, whilst the decline in leprosy incidence may also have contributed. Additional research is needed to understand the evolution of traditional taboos in Suriname and the Greater Caribbean.